Development of Contact Lens Suitability System (ClenSyst) - Muhammed Hafiza, Syaratul Ain; Sahari @ Ashaari, Noraidah; Che Hamzah, Jemaima; Razak, Syariza (2009)
This paper proposes a system that can determine the suitability of contact lenses usage.The aim of this work is to provide a decision making system by using the application of fuzzy logic to analyze and decide the appropriate type of contact lenses based on the corneal condition, astigmatism, reason and environment of the patient.A corneal topography is used to give information on corneal power and astigmatism measurement.The expected output of the system is suitability of using contact lenses, corneal power and the type of contact lens.